Effects of sequential inhibitory and facilitatory repetitive transcranial magnetic stimulation on neurological and functional recovery of a patient with chronic stroke: A case report and literature review - Chen, Nan; Qiu, Xiao; Hua, Yan; Hu, Jian; Bai, Yulong (Frontiers in Neurology, 2023)
Background and purpose The effects of conventional protocols of repetitive transcranial magnetic stimulation (rTMS) in the chronic phase of stroke are limited. This study aimed to apply the sequential inhibitory and facilitatory rTMS for upper limb motor dysfunction post-stroke to observe the efficacy and explore the possible neurophysiological mechanism. We hypothesize that this protocol would both enhance the excitability of affected M1 and promote connections among motor areas. Case description We reported a 55-year-old female patient with a 1-year chronic stroke and right-sided hemiplegia, who underwent the 14-session rTMS with seven sessions of low frequency (LF) and with seven sessions of high frequency (HF). Clinical scales mainly including Fugl-Meyer Assessment of Upper Extremity (FMA-UE), Action Research Arm Test (ARAT), neurophysiological measures, and functional near-infrared spectroscopy (fNIRS) were assessed before (T0), at the midpoint (T1), and after the intervention (T2). Outcomes The patient exhibited post-intervention improvement in upper extremity function. There was increased excitability in the ipsilesional hemisphere and the opposite in the contralesional hemisphere. The interhemispheric inhibition (IHI) ratio increased from 2.70 to 10.81 and finally decreased to 1.34. Oxy-Hb signal was significantly decreased in affected M1 and mildly decreased in unaffected M1, while that of PMC and SMA on the affected side increased significantly. Conclusion The sequential inhibitory and facilitatory rTMS significantly promoted motor recovery in the patient. Related mechanisms include upregulation of excitability in the ipsilesional hemisphere, return of interhemispheric balance, and neuroplasticity-induced cortical reorganization.